Personal Problem encountered by English Students in Graduation On Time - Jopian Rhomiko Yudistira; washlurachim safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The objective of the research was to find out the personal problem encountered by English Students in graduation on Time at Muhammadiyah University of Bengkulu. The design of this research was descriptive method. The instrument of the research was questionnaire. The questionnaire was based on based on Dieters (2013) about factors of the Personal Problem Encountered by English Students In Graduation on Time. The result showed that from six factors of the students problem to graduate on time, they are: Students Experience, Program Choice, Social Environment, Demands of the Program, Financial Consideration, Instutional Factors there are three factors that affect the students problem to graduate on time, they are, demands of the program, program choice and students experience. From the result, the researcher will give suggestion for the students: It is suggested the students have to have high motivation to finish their study and graduation on time because when the students have high motivation it can make them be active to learn. The students also have to try be brave to communicate and ask something about material or thesis with their lecturer. Key words: Graduation, Students Problem to Graduate on time